Intercollegiate Athletes - Cotrufo, Raymond J. (Sports Leadership: A Concise Reference Guide, 2015)

NFL Evolution: Does Prioritizing Player Welfare Influence Consumers? - Cotrufo, Raymond J.; Burton, Laura J. (International Journal of Sport Management, 2016)
NFL Evolution is a Corporate Social Responsibility (CSR) program designed to improve the health and safety of football participants at all levels (NFLEvolution. com). Though sport-based CSR initiatives are generally well-received by the public, the internal focus of this particular initiative may affect consumers differently. Using data provided by a sample of university students via an online survey, regression analysis was used to determine if this program affected their intentions to consume NFL-related products and media. Results showed that this form of CSR initiative may influence consumption behaviors, especially related to media consumption and intentions to discuss the NFL with others. ABSTRACT FROM AUTHOR
Keywords: NATIONAL Football League; REGRESSION analysis; SOCIAL responsibility of business; dept.rec

National Collegiate Academic Association? The implications of increased NCAA oversight of academics - Trachsler, Tracy A.; Cotrufo, Raymond J. (Journal of Contemporary Athletics, 2017)
Keywords: dept.rec; ⛔ No DOI found

The Ultimate Penalty Box: Fayetteville-Manlius is Disqualified from the State Playoffs for Playing Too Many Games: Editor: Thomas H. Sawyer - Dodds, Mark A.; Cotrufo, Raymond J. (Journal of Physical Education, Recreation & Dance, 2015)
Instead of playing in the state tournament, the Fayetteville-Manlius boy's hockey team was disqualified because they played too many games. The New York State Public High School Athletic Association limits hockey teams to 20 regular season games, but Fayetteville-Manlius mistakenly considered one of its competitions to be a scrimmage instead of a regular season game.
Keywords: dept.rec; peer-reviewed

The Experiences of Female Athletic Trainers in the Role of the Head Athletic Trainer - Mazerolle, Stephanie M.; Burton, Laura; Cotrufo, Raymond J. (Journal of Athletic Training, 2015)
Very few women have leadership positions in athletic training (ie, head athletic training positions) in intercollegiate athletics. Research exists on the barriers to attaining the role; however, our understanding about the experiences of those currently engaged in the role is limited.To examine the experiences of female head athletic trainers as they worked toward and attained the position of head athletic trainer.Qualitative study.National Collegiate Athletic Association Division I setting.Eight female athletic trainers serving in the role of head athletic trainer participated in our study. The mean age of the participants was 45 ± 12 years, with 5 ± 1.5 years of experience in the role of head athletic trainer and 21 ± 10 years of experience as athletic trainers.We conducted phone interviews with the 8 participants following a semistructured format. Interviews were transcribed verbatim and analyzed following a general inductive approach as described by Thomas. To establish credibility, we used a peer reviewer, member checks, and multiple-analyst triangulation.Six major themes emerged from our analysis regarding the experiences of female head athletic trainers. Opportunities to become a head athletic trainer, leadership qualities, and unique personal characteristics were discussed as factors leading to the assumption of the role of the head athletic trainer. Where women hold back, family challenges, and organizational barriers speak to the potential obstacles to assuming the role of head athletic trainer.Female head athletic trainers did not seek the role, but through persistence and encouragement, they find themselves assuming the role. Leadership skills were discussed as important for success in the role of head athletic trainer. Life balancing and parenting were identified as barriers to women seeking the role of head athletic trainer.
Keywords: dept.rec; peer-reviewed

Positive Youth Development: Minority Male Participation in a Sport-Based Afterschool Program in an Urban Environment - Fuller, Rhema D.; Percy, Vernon E.; Bruening, Jennifer E.; Cotrufo, Raymond J. (Research Quarterly for Exercise and Sport, 2013)
Purpose As there is little research that investigates the experiences of minority boys participating in youth development programs (Fashola, 2003), the current research focused on a sport-based youth development program for early adolescent Black and Latino boys in Hartford, CT. Specifically, the present study explored (a) what attracted minority boys to participate in youth development programs, (b) what kept them involved, and (c) whether their involvement translated into positive developmental outcomes. Method The study used semistructured individual interviews to collect data from 8 participants and their parents. The research team deductively coded interviews in accordance with the a-priori framework of the Five Cs and Sixth C of youth development (i.e., competence, character, caring, confidence, connection, and contribution; Roth & Brooks-Gunn, 2003). In addition, interviews were deductively coded to investigate why participants became involved in the program and why they continued participation. Results Findings from the study indicated that participants became involved with the Sport Hartford Boys (SHB) program mainly due to its emphasis on sport-related activities. Moreover, findings related to the youths' continued involvement revealed their value for the SHB program as a safe place that kept them out of trouble and provided experiences that led to positive personal development. Furthermore, results indicated that participation in the program facilitated the development of each “C” of youth development. Conclusion By promoting positive relationships and providing opportunities for self-exploration in a safe and trusting environment, afterschool programs can cultivate positive youth development in minority boys, at least in the short term.
Keywords: dept.rec; identity development; mentoring; peer-reviewed; sport-based youth development; youth programs

Applying Intergroup Contact Theory to the Sport Management Classroom - Bruening, Jennifer; Fuller, Rhema D.; Cotrufo, Raymond J.; Madsen, Rachel M.; Evanovich, Justin; Wilson-Hill, Devon E. (Sport Management Education Journal, 2014)
Allport’s (1954) intergroup contact hypothesis states that interactions with members of an out-group, particularly of a different racial and/or ethnic group, are effective in changing attitudes about diversity (Allport, 1954; Pettigrew, 1998). In this study, the intergroup contact hypothesis was applied to the design of a sport management course. The classroom component focused the role of sport in education, health, and leadership development, and the application was structured sport and physical activity programming with school-age children at several urban sites. Data were gathered from 91 college students over 3 years about course-related experiences and how the students’ backgrounds influenced their social identities and understanding of out-group members. Results showed that intergroup contact effectively assisted in developing understanding and cooperation and reducing negative attitudes between groups. The participants received diversity education, via intergroup contact, both inside and outside the classroom, which will potentially equip them to take proactive strategies when managing organizational diversity in the sport industry.
Keywords: dept.rec